Battling Eight Giants : Basic Income Now. - Standing, Guy (London [England] : I.B. Tauris & Company, Limited, 2020)
"Today in one the richest countries in the world, 60% of households in poverty have people in jobs, inequality is the highest it has been for 100 years, climate change threatens our extinction and automation means millions are forced into a life of precarity. The solution? Basic Income. Here, Guy Standing, the leading expert on the concept, explains how to solve the new eight evils of modern life, and all for almost zero net cost. There is a better future, one that makes certain all citizens can share in the wealth of the modern economy. Far from being a new idea, Standing shows how the roots of basic income go back to the Charter of the Forest, one of two foundational documents of the state ? the other, sealed on the same day, being the Magna Carta. All citizens have a right to the wealth created by capitalism, and all ? left or right, rich or poor ? can benefit from a dynamic and ecologically grounded economy created by the guarantee of subsistence to all."--
Intro -- Title Page -- Copyright Page -- Contents -- Acknowledgements -- Chapter 1: Slaying giants with basic income -- Defining basic income -- Why is basic income needed? -- Slaying the eight modern giants -- Chapter 2: The immorality of Universal Credit -- Reviving and enhancing disability benefits -- Chapter 3: Why basic income beats the alternatives -- Answering the objections -- Chapter 4: Piloting basic income in Britain -- What should be piloted? -- How should basic income pilots be designed? -- Where should pilots be conducted? -- Chapter 5: Taking the first steps
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Print version record.
Keywords: Basic income; Income distribution; Poverty; Politics & government; Electronic books